2015
DOI: 10.1021/jp512545c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Optimizing Microemulsions with Magnetic Room Temperature Ionic Liquids (MRTILs)

Abstract: Nonaqueous microemulsions containing the magnetic room temperature ionic liquid (MRTIL) bmimFeCl4 as polar phase were studied with respect to their macroscopic phase behavior and structure by means of small angle neutron scattering (SANS). The phase behavior was studied in detail for different alcohols as cosurfactant and different oils as nonpolar phase and mainly by varying the chain length of the used ionic surfactant (CnmimCl with n = 14, 16, 18). In general, phase behavior and structural ordering in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…Therefore, recent efforts have dedicated on the formulation of cosurfactant‐free microemulsion or RMs with biocompatible excipients. Also, SAILs used so far for preparation of RMs mainly contain imidazolium cations, which might cause environmental hazards when released through waste‐water effluents . Therefore, toxicity and biodegradation remain crucial concerns while dealing with the ILs, and the search for synthesis of more greener ILs in terms of toxicity and biodegradability is growing day by day .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recent efforts have dedicated on the formulation of cosurfactant‐free microemulsion or RMs with biocompatible excipients. Also, SAILs used so far for preparation of RMs mainly contain imidazolium cations, which might cause environmental hazards when released through waste‐water effluents . Therefore, toxicity and biodegradation remain crucial concerns while dealing with the ILs, and the search for synthesis of more greener ILs in terms of toxicity and biodegradability is growing day by day .…”
Section: Introductionmentioning
confidence: 99%
“…Detailed investigations oen rely on small-angle neutron scattering (SANS), which is time-consuming and costly and suffers from poor availability. 27,30,31,[45][46][47] Moreover, SANS is only of limited value for following kinetically fast processes which would be desirable for the live monitoring of structural changes occurring in solution. Optical birefringence is a well-established method to monitor the dynamic response of materials to external elds.…”
mentioning
confidence: 99%
“…Last decade, two rather special subclasses of ILs, magnetic ionic liquids (MILs) and magnetic ionic liquids surfactants (MILSs), were generated and received increased attention. MILs are ILs with magneto-responsivity usually caused by metal complex ions, and MILSs are MILs with surface-active properties that are provided by an alkyl chain usually with ten or more carbon atoms . As molecular liquids, MILs and MILSs have advantages over traditional ferrofluids that usually need a flammable organic carrier fluid.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, very few attempts have shown that MILs and MILSs are able to formulate magnetic microemulsions (MMEs) as the polar or surfactant component, respectively, and these MMEs exhibit unexpected high magnetic responsiveness and magnetic susceptibility, thus suggesting promising potential applications based on external magnetic field inspired manipulation, e.g., environment cleanup, water treatment, separation, oil recovery, targeted drug delivery, and so on. However, studies about MMEs are still rather scarce to date.…”
Section: Introductionmentioning
confidence: 99%